Aflatoxin-Contaminated Nut Separation by Applied Machinery and Processing Stages in Fresh Pistachio Processing Plant - Hadavi, Ebrahim; Feizi, Hamid; Gheibi, Behrouz (Frontiers in Microbiology, 2017)
In pistachio nuts, aflatoxin is mainly concentrated in the green hull-cracked nuts in the orchard even prior to harvest. However, during the hull-removal process, the hulls of all nuts including the cracked, identifiable nuts are removed causing an important characterization criterion of the contaminated nuts, to be lost. This, in turn, makes it harder to detect the contaminated nuts. However, during the processing stage, there is a good possibility of sorting the contaminated nuts based on their other inherent features, such as specific gravity and stain on the hard shell. In this study, we aimed to explore the effect of applied processing machinery and related sequences in the aflatoxin flow during postharvest processing and the possible ways of reducing aflatoxin contamination in the Iranian pistachio industry. We planned a systematic sampling from the main and reject streams in two major prevailing processing methods, namely, wet and dry. In the dry processing method, the reject streams such as the adhering-hull rejects, air floaters, and manual hand pick-outs from the final inspection were found to be significantly more contaminated than the main stream. However, in the wet processing method, the input stream was considered highly contaminated. Among the sorting stages, only the adhering-hull rejects of the sinkers were considered more contaminated than the main stream. A contamination removal index was developed and applied to compare the effectiveness of the processing procedures. The water flotation tank was deemed responsible for 52.5% of aflatoxin contamination removal compared to 2.1% in the air flotation system. More effective sorting was achieved by the adhering-hull remover, which was preceded by a rubber-drum huller instead of the metal-drum type. Thus, by combining the most effective techniques of aflatoxin removal, an improved and more efficient method may be designed for pistachio processing plants.